FITRAT - TEXTOLOGIST (Based on the complex "Examples of Uzbek literature") - Tanju Seyhan,; Hamroyeva Orzigul Jalolovna, (Academia Science Repository, 2023)
Abdurauf Fitrat, one of the leading representatives of Jadidchilik movement, deeply understood that the essence of this movement is to convey the spiritual wealth of the people, manuscript works to the people. That's why he created serious researches with the aim of making the classical works known to the people and the people of science and to retrieve these sources. Excerpts from classic works of the scientist's "Examples of Uzbek Literature" complex are examples of this research. The article focuses on Fitrat's scientific research related to the manuscripts he acquired during his studies in Turkey and the publications of the same period.